2012
DOI: 10.5051/jpis.2012.42.6.243
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of magnetostrictive and piezoelectric ultrasonic scaling devices: an in vitro study

Abstract: PurposeThe effects of magnetostrictive and piezoelectric devices on tooth surfaces seem to differ with regard to the root surface roughness they produce. This study aimed to compare the results of scaling using magnetostrictive and piezoelectric devices on extracted teeth.MethodsForty-four human extracted teeth were assigned to four study groups (n=11). In two groups (C100 and C200), the teeth were scaled using a magnetostrictive device and two different lateral forces: 100 g and 200 g, respectively. In the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
(18 reference statements)
2
20
0
Order By: Relevance
“…Similarly, at 45 • , the magnetostrictive ultrasonic scaler applied with medium power resulted in a surface almost twice as smooth as the piezoelectric ultrasonic scaler applied with full power (MaM45 = 0.14 ± 0 µm and PiF45 = 0.27 ± 0 µm, respectively). These findings were in line with the studies suggesting different surface roughness results are due to differences in adjusted lateral force, tip angulation, and power settings [11,12,24,32]. On the other hand, in our study, the ultrasonic scaler type did not significantly influence surface roughness.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similarly, at 45 • , the magnetostrictive ultrasonic scaler applied with medium power resulted in a surface almost twice as smooth as the piezoelectric ultrasonic scaler applied with full power (MaM45 = 0.14 ± 0 µm and PiF45 = 0.27 ± 0 µm, respectively). These findings were in line with the studies suggesting different surface roughness results are due to differences in adjusted lateral force, tip angulation, and power settings [11,12,24,32]. On the other hand, in our study, the ultrasonic scaler type did not significantly influence surface roughness.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, in our study, the ultrasonic scaler type did not significantly influence surface roughness. This result was inconsistent with the limited number of comprehensive studies in the literature, particularly those comparing the surface roughness effects of the magnetostrictive and piezoelectric ultrasonic scalers suggesting differences are due to varying impacts [11,13]. Busslinger et al [13] reported that the piezoelectric ultrasonic scaler was more efficient than the magnetostrictive ultrasonic scaler in eliminating calculus but left the instrumented surface rougher.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Powerdriven scalers should be used carefully because of the risks for both the patient and dentist/hygienist (Gorrel 2004;Niemiec 2013). Most studies consider magnetostrictive and piezoelectric scalers to be equal or only marginally different with respect to risks (Yousefimanesh 2012), although sonic scalers are sometimes considered to be less dangerous (Caiafa 2007). In vitro studies indicate that the scaler tips produce heat which could be dangerous for the vitality of the dental pulp (Lea et al 2004).…”
mentioning
confidence: 99%